Differential Dependence of StpA on H-NS in Autoregulation of stpA and in Regulation of bgl - Wolf, Tinka (American Society for Microbiology, 2006)
StpA has functional similarity to its homologue, the nucleoid structuring protein H-NS. It binds to AT-rich, planar, bent DNA and constrains DNA supercoils. In addition, StpA acts as an RNA chaperone. StpA and H-NS also form heterodimers. However, cellular levels of StpA are low due to repression of stpA by H-NS and negative autoregulation. Here we show that effective (30-fold) repression of stpA transcription requires a downstream regulator element located within the stpA coding region. In addition, we show that StpA represses stpA threefold in an hns null mutant. In contrast, repression of the bgl operon, another H-NS-repressed system, is not achieved by StpA alone. It becomes StpA dependent in the presence of a fusion protein encompassing the N-terminal 37 amino acids of H-NS, which comprise the core of the dimerization domain. StpA also effectively complements H-NS-I119T, a mutant defective in specific DNA binding, in repression of the bgl operon. Thus, StpA complements H-NS proteins defective in DNA binding to repress bgl, while in autoregulation of stpA it acts autonomously, indicating a difference in the mechanisms of repression.